Prevalence and factors associated with female genital mutilation/cutting among Tanzanian women who gave birth in the five years prior to the survey: A population-based study. - Fabiola Vincent Moshi (PLoS ONE)
Background Female Genital Mutilation/Cutting (FGM/C) poses a significant public health challenge in developing countries, leading to increased risks of adverse obstetric outcomes such as caesarean section, postpartum hemorrhage, episiotomy, difficult labor, obstetric tears/lacerations, instrumental delivery, prolonged labor, and extended maternal hospital stays. The study aimed to determine the prevalence and factors associated with FGM/C among Tanzanian women who had given birth within five years preceding the Survey. Method This study utilized an analytical cross-sectional design based on data from the 2015-2016 Tanzania Demographic and Health Survey and Malaria Indicators Survey (TDHS-MIS). A total of 5,777 women who had given birth within the five years preceding the survey and who provided responses to questions regarding female circumcision were included in the analysis. Descriptive analysis was employed to examine the prevalence of FGM/C among women in Tanzania. Additionally, multiple logistic regression was used to identify factors associated with FGM/C within this population. Results The prevalence of FGM/C was 12.1% at 95%CI of 11.3% to 13%. Factors associated with FGM/C were marital status [married (AOR = 3.141 at 95%CI = 1.757-5.616,p<0.001), living with male partners (AOR = 2.001 at 95%CI = 1.082-3.699, p = 0.027), widowed (AOR = 2.922 at 95%CI = 1.201-7.111, p = 0.03)] never in union a reference population; wealth index [poorest (AOR = 2.329 at 95% CI = 1.442-3.763, p = 0.001), middle (AOR = 1.722 at 95% CI = 1.075-2.758, p = 0.024), richer (AOR = 1.831 at 95%CI = 1.205-2.781, p = 0.005)] in reference to richest women; zones [Northern zone, (AOR = 91.787 at 95%CI = 28.41-296.546, p<0.001), central zone, (AOR = 215.07 at 95%CI = 67.093-689.423,p<0.001), southern highlands, (AOR = 12.005 at 95% CI = 3.49-41.298, p<0.001), lake zone (AOR = 13.927 at 95%CI = 4.338-44.714,p<0.001), eastern zone, (AOR = 24.167 at 95% CI = 7.299-80.017, p<0.001)]; place of childbirth [outside health facility (AOR = 1.616 at 95%CI = 1.287-2.03, p<0.001)] in reference to health facility childbirth; parity [para 5+ (AOR = 2.204 at 95% CI = 1.477-3.288,p<0.001)] para one a reference population; and opinion on whether FGM/C stopped or continued [continued (AOR = 8.884 at 95% CI = 5.636-14.003, p<0.001). Conclusion This study underscores the persistent issue of FGM/C in Tanzania, particularly among married women, those from lower-income households, and those living in regions with high prevalence. Women giving birth outside health facilities and those with multiple children are at higher risk. The study emphasizes the need for targeted interventions addressing socio-cultural factors, alongside providing legal, healthcare, and psychological support to those affected. Educational campaigns and community engagement, especially with traditional and religious leaders, are crucial for challenging cultural beliefs and reducing FGM/C's prevalence.